0148 Self-motivated learning with gamification improves and maintains CPR performance, a randomised controlled trial. (2nd November 2015) - MacKinnon, Ralph; Stoeter, Rachel; Doherty, Catherine; Fullwood, Catherine; Stenfors-Hayes, Terese; Cheng, Adam; Nadkarni, Vinay; Chang, Todd
Abstract : Background: Effective paediatric basic life support improves survival and neurological outcomes. 1 Current CPR training involves 4-yearly courses plus annual updates, yet skills degrade significantly by 3–6 months. 2, 3 To date, no method has been described to motivate frequent and persistent CPR practice. To achieve this we explored the use of competition and peer pressure, as a gamification technique, to increase CPR usage and performance. Methodology: We performed a prospective, randomised controlled trial to assess the effect of self-motivated gamification-based learning on CPR skills over time. 170 participants of all grades of healthcare from theatres and PICU were randomised to unlimited access to a work-place based infant CPR manikin providing immediate feedback on CPR performance or to the control group without such access. The manikin calculated a compression score based on rate, depth, hand position and release and a ventilation score from rate and volume, developed collaborating with the American Heart Association. 4 Overall scores for each two minute session were calculated by averaging compression and ventilation scores. Participant scores were ranked anonymously on monthly updated leaderboards, posted close to the manikin. Baseline and final 6-month scores were compared via paired Wilcoxon tests. For participants not motivated to continue for 6 months, their last recorded score was taken as a final score. Results: 91 participants were in the intervention group (53.5%) and 79 (46.5%) the control group with no notable demographical differences between the two arms. The median (IQR) baseline scores for the control and intervention groups respectively were 47.0 (31.75–63.00) and 47.5 (33.50–63.00). The median 6 month scores for the control and intervention groups respectively were 47.0 (34.50–58.25) and 62.0 (42.00–81.75). Conclusion: CPR performance in the intervention group improved significantly over the 6-month period (p < 0.001), compared with the control, suggesting that self-motivated, gamification-based CPR training can improve quality of CPR over time. References: Abella BS, Sandbo, N, Vassilatos P, et al . Chest compression rates during cardiopulmonary resuscitation are suboptimal: a prospective study during in-hospital cardiac arrest. Circulation 2005;1(111):428–34 Na JU, Sim MS, Jo IJ, Song HG, Song KJ. Basic life support skill retention of medical interns and the effect of clinical experience of cardiopulmonary resuscitation. Emerg Med J. 2012;29(10):833–7 Hamilton R. Nurses' knowledge and skill retention following cardiopulmonary resuscitation training: a review of the literature. J Adv Nurs. 2005;51(3):288–97 Laerdal Inc. CPR scoring explained 2013. http://cdn.laerdal.com/downloads/f2729/Scoring_CPR_November_v2.pdf